Etiology of jackfruit (Artocarpus heterophyllus Lam.) bronzing disease in Peninsular Malaysia - Gan, Hwee Yiam (2017)
Jackfruit (Artocarpus heterophyllus Lam.) is a popular tropical fruit cultivated in Malaysia and is classified under the family of Moraceae. Unfortunately, jackfruit has been found susceptible to the damage bronzing disease since 2008, which can be visualised from the rust coloured specks or streaks appearing on the pulps, rags and seed membrane of the fruit. This predicament has extended to causing the bulbs bear an unpleasant taste and appears asymptomatic from the outer fruit surface. Many possibilities on the potential causative factors have been brought up by several research agencies. Not at least, an important report on similar disease symptoms was described and concluded that the bacteria, namely Pantoea stewartii to have caused the bronzing disease in the Philippines recently. At present, research approaches to identify the causal agents and the effect of the disease on jackfruit are still scanty. Thus, the purpose of this study was to identify the biotic causal agent of the jackfruit bronzing disease from samples collected in Peninsular Malaysia using morphological, biochemical and molecular identification, (ii) to conduct pathogenicity test of the suspected causal agents on the susceptible variety ‘Tekam Yellow’ (J33) and (iii) to elucidate the infection process of jackfruit bronzing by histological examination of infected tissue using scanning electron microscope (SEM). For disease incidence (DI) survey, a total of 59 jackfruits were sampled randomly from five states in Peninsular Malayisa i.e. Perak, N. Sembilan, Pahang, Johor and Selangor in this study. The result showed that the disease incident (DI) of fruit bronzing on jackfruit was high, ranging from at least 20% to 70%. For isolation and identification, a total of 15 samples of fruit with bronzing symptoms were collected from 8 locations in three states in Malaysia. Total of 120 bacteria colonies with dark yellow pigment were observed during isolation plating of all samples. Morphologically, this bacterium is Gram negative, oxidase negative, appeared as a non-capsulated straight rod with an average of 0.35 (width) x 1.31 (length) μm, facultative anaerobic short-rod. BIOLOG GEN III has identified 26 isolates as Pantoea sp. while the molecular data, produced through DNA sequence analysis on the two selected 16S rRNA gene universal primer (B27F and U1492R) using Basic Local Alignment Search Tool (BLAST) of which all the 15 isolates as P. stewartii and 1 isolates as P. dispersa which showed 99-100% similarity. However, from established phylogenetic tree fifteen isolates were grouped in the same cluster with P. stewartii and distinct from P. ananatis and P. dispersa. The result has further clarified that the isolate that caused fruit bronzing is P. stewartii. From pathogenicity test, the two selected P. stewartii isolates UPM 001 and P. stewartii isolates UPM 002 were confirmed to produce the same type of symptom as observed in the field samples. The pathogens were successfully re-isolated from the bronzing symptom of inoculated parts like rags and bulbs, thus fulfilling Koch’s postulates and confirmed that P. stewartii as a jackfruit pathogen in Malaysia. Besides, natural opening such as stomata was foreseen to be the possible pathway taken by P. stewartii for the intrusion into the fruit.